Gamma Knife Radiosurgery for Cerebellopontine Angle Meningiomas: A Multicenter Study. Issue 4 (3rd July 2014) - Ding, Dale; Starke, Robert M.; Kano, Hideyuki; Nakaji, Peter; Barnett, Gene H.; Mathieu, David; Chiang, Veronica; Omay, Sacit B.; Hess, Judith; McBride, Heyoung L.; Honea, Norissa; Lee, John Y.K.; et al.
Abstract: BACKGROUND: Resection of cerebellopontine angle (CPA) meningiomas may result in significant neurological morbidity. Radiosurgery offers a minimally invasive alternative to surgery. OBJECTIVE: To evaluate, in a multicenter cohort study, the outcomes of patients harboring CPA meningiomas who underwent Gamma Knife radiosurgery (GKRS). METHODS: From 7 institutions participating in the North American Gamma Knife Consortium, 177 patients with benign CPA meningiomas treated with GKRS and at least 6 months radiologic follow-up were included for analysis. The mean age was 59 years and 84% were female. Dizziness or imbalance (48%) and cranial nerve (CN) VIII dysfunction (45%) were the most common presenting symptoms. The median tumor volume and prescription dose were 3.6 cc and 13 Gy, respectively. The mean radiologic and clinical follow-up durations were 47 and 46 months, respectively. Multivariate regression analyses were performed to identify the predictors of tumor progression and neurological deterioration. RESULTS: The actuarial rates of progression-free survival at 5 and 10 years were 93% and 77%, respectively. Male sex ( P = .014), prior fractionated radiation therapy ( P = .010), and ataxia at presentation ( P = .002) were independent predictors of tumor progression. Symptomatic adverse radiation effects and permanent neurological deterioration were observed in 1.1% and 9% of patients, respectively. Facial spasms at presentation ( P = .007) and lower maximal dose ( P = .011) were independently associated with neurological deterioration. CONCLUSION: GKRS is an effective therapy for CPA meningiomas. Depending on the patient and tumor characteristics, radiosurgery can be an adjuvant treatment to initial surgical resection or a standalone procedure that obviates the need for resection in most patients.